(3GdhGajI aj TQM GdcGajIs - (3GdESJQGHGPj GdSefGFj GdfLaj GdQVj, GdQVj, fLe GdOjf, eMeO Hf GdMSf, J fMh (B686(3g`s ((3MSjf Hf fUjQs)
(3ChdgG (B:s
(3CMeO Gddg Ydi YXeI LdGdg(B...(3aEfj HYO Cf TQMJ cJGH GdcGajI aj GdfMh(B...(3TQMJg KGfjG ebJUQG Ydi Md CdaGXg(B...s
(3BNQgG (B:s
(3aEfc EPG bdJ aj jG RjOhf GVQHf GVQHhG aj hba(B...(3hgPG BNQ GdcdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B86s
(3cTa GdXfhf(B:(3L(B2(3,U(B1370s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs